Perirenal fat thickness is associated with metabolic risk factors in patients with chronic kidney disease (2019)
Adipose tissue accumulation in specific body compartments has been associated with diabetes, hypertension and dyslipidemia. Perirenal fat (PRF) may lead to have direct lipotoxic effects on renal function and intrarenal hydrostatic pressure. This study was undertaken to explore the association of PRF with cardiovascular risk factors and different stages of chronic kidney disease (CKD). We studied 103 patients with CKD of different stages (1 to 5). PRF was measured by B-mode renal ultrasonography in the distal third between the cortex and the hepatic border and/or spleen. The PRF thickness was greater in CKD patients with impaired fasting glucose than in those with normal glucose levels (1.10 ± 0.40 cm vs. 0.85 ± 0.39 cm, P < 0.01). Patients in CKD stages 4 and 5 (glomerular filtration rate [GFR] < 30 mL/min/1.73 m2) had the highest PRF thickness. Serum triglyceride levels correlated positively with the PRF thickness; the PRF thickness was greater in patients with triglyceride levels ≥ 150 mg/dL (1.09 ± 0.40 cm vs. 0.86 ± 0.36 cm, P < 0.01). In patients with a GFR < 60 mL/min/1.73 m2, uric acid levels correlated positively with the PRF thickness (P < 0.05). In CKD patients, the PRF thickness correlated significantly with metabolic risk factors that could affect kidney function.